1998
DOI: 10.1021/cm980742f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis for the Control of γ-Fe2O3 Nanoparticle Size. Morphology, Microstructure, and Magnetic Behavior

Abstract: The electrochemical synthesis of nanoparticles of γ-Fe2O3 was performed in an organic medium. The size was directly controlled by the imposed current density, and the resulting particles were stabilized as a colloidal suspension by the use of cationic surfactants. The size distributions of the particles were narrow, with the average sizes varying from 3 to 8 nm. The amorphous character of the nanoparticles was clearly established by X-ray powder diffraction and TEM analysis. The microstructure of this phase co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
169
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(178 citation statements)
references
References 27 publications
8
169
0
1
Order By: Relevance
“…Interestingly, it has been observed that D TEM for T33 (8.2 nm) is smaller than D mag (9.86 nm) i.e., magnetic size is overestimated by approximately 10% in comparison to TEM size. Such overestimation was previously observed by few researchers and can be explained on the basis of either perturbation in the Langevin function caused by interparticle interactions that was ignored during tting 51 or the consideration of single size distribution of the particles. In order to get a better information, the magnetic sizes (D mag ) were also calculated by using eqn (7), 52,53 …”
mentioning
confidence: 75%
“…Interestingly, it has been observed that D TEM for T33 (8.2 nm) is smaller than D mag (9.86 nm) i.e., magnetic size is overestimated by approximately 10% in comparison to TEM size. Such overestimation was previously observed by few researchers and can be explained on the basis of either perturbation in the Langevin function caused by interparticle interactions that was ignored during tting 51 or the consideration of single size distribution of the particles. In order to get a better information, the magnetic sizes (D mag ) were also calculated by using eqn (7), 52,53 …”
mentioning
confidence: 75%
“…et al, 2002), (ii) hydrogen gas as a reducing agent of iron hydroxide (Franger S. et al, 2004;Manrique-Julio J. et al, 2016;Melnig V. and Ursu L., 2011), (iii) direct reaction between Fe 2+ and Fe 3+ (Karami H. and Chidar E., 2012;Ying T.Y. et al, 2002), and (iv) oxygen as oxidant agent and subsequent in-solution precipitation Gopi D. et al, 2016;Lozano I. et al, 2017;Pascal C. et al, 1999;Starowicz M. et al, 2011).…”
Section: Mechanism Of Particle Formationmentioning
confidence: 99%
“…c-Fe 2 O 3 (Maghemite) nanocrystallites is a red-brown material which has attracted great interest due to its variety of technological applications in modern industry [1][2][3][4][5][6]. It possesses various optical, electrical, and magnetic properties and has been used in color imaging, biochemical separations, information storage, gas sensors, catalysts, ferrofluids, pigments, etc.…”
Section: Introductionmentioning
confidence: 99%